PENGARUH PEMBERIAN SARI KULIT NANAS (Ananas comosus (L) Merr) TERHADAP JUMLAH KOLONI BAKTERI PADA IKAN BANDENG (Chanos chanos F.) - Zainal Berlian; Fitratul Aini; Melda Yunita (Florea : Jurnal Biologi dan Pembelajarannya, 2016)
Pineapple rind (Anana chomosus (L) Merr) is household waste has not been used optimally. Rind the  pineapple contains bromelain enzymes, citric acid and phenols, to inhibit bacterial growth. The research objective test ativitas antibacterial (Ananas chomosus (L) Merr) to fish. The study design used a completely randomized design (CRD), the treatment of P0 (0%), P1 (12.5%), P2 (25%), P3 (50%) and P4 (100%). Results of analysis of variance (ANOVA), the concentration extract pineapple rind (Anana chomosus (L) Merr) gives significant differences (p> 0.01) to the number of bacterial colonies, where Fh > Ft. The results showed pineapple rind (Anana chomosus (L) Merr) has antibacterial activity